Professional identity among Pakistani aviation medicine specialists in KSA: a qualitative study - Malik, Raad Nadeem (2024)
Although the military and commercial aviation industries are relatively new, they have experienced significant innovations and developments. The Pakistan Air Force (PAF) maintains one of the largest air forces globally, with aviation specialists performing demanding operational commitments and deployments around the clock. Aviation medicine specialists, also known as flight surgeons, play a crucial role in the health and well-being of PAF aircrew and technical ground crew, ensuring their flying fitness. However, to date, no study has examined the professional identity of flight surgeons in Pakistan's aviation sector. This study explores the professional identity of Pakistani Aviation Medicine Specialists in the Kingdom of Saudi Arabia. A qualitative design was employed, with thematic analysis as the selected method for analysis. Pakistan Air Force male flight surgeons with a minimum of five years of experience in the field were recruited. The study included 13 participants, selected through purposive sampling. Participants provided consent after reviewing an information sheet that described the study. Four main themes emerged which are, 1) professional identity in aviation medicine, 2) qualities of a good aviation medicine specialist, 3) becoming a successful aviation medicine specialist, and 4) professionalism and willingness. Interviews with experienced flight surgeons were analyzed to understand their professional identity. Each subtheme was discussed in relation to the doctors' experiences. The thematic analysis clarifies a heterogeneous landscape characterized by dynamic obstacles and specific requirements in the field of aviation medicine. The identified themes highlight the unique needs of the military aviation sector, emphasizing the importance of evidence-based approaches, collaborative methods, and a commitment to continuous learning. The study reveals the delicate balance required between medical and operational success, stressing effective communication, collaboration, and prompt action. The concept of professionalism and enthusiasm stands out, demonstrating a commitment to ethical standards and active involvement. The study underscores the importance of tenacity, devotion, and adaptation in the evolving field of aviation medicine, emphasizing its critical role in ensuring the safety and welfare of aircrew.